PENGARUH LITERASI KEUANGAN DAN SOSIALISASI KEUANGAN (P2K2) TERHADAP PENGELOLAAN KEUANGAN KELUARGA PENERIMA MANFAAT (KPM) PROGRAM KELUARGA HARAPAN (PKH) KECAMATAN WATUNOHU - Arini Amanda Riswan; Fitri Kumalasari; Agus Zulbay (Komunitas Manajemen Kompetitif, 2026)
This study aims to determine the effect of financial literacy and financial socialization (P2K2) on financial management among Beneficiary Families (KPM) of the Family Hope Program (PKH) in Watunohu District, North Kolaka Regency. This research uses a quantitative approach with Partial Least Square (PLS) analysis. The population in this study were PKH beneficiary families in Watunohu District, while the sample consisted of 159 respondents selected using purposive sampling techniques. The results showed that financial literacy has a positive and significant effect on financial management. This indicates that the higher the level of financial literacy possessed by beneficiary families, the better their ability to manage household finances. Financial socialization (P2K2) also has a positive and significant effect on financial management because the socialization process is able to increase awareness, understanding, and financial management skills among PKH beneficiary families. Simultaneously, financial literacy and financial socialization contribute significantly to improving household financial management. Therefore, strengthening financial education and optimizing financial socialization activities are important strategies in improving the welfare of PKH beneficiary families.